Assessment of learners’ attitude in Social Sciences and its correlation to their Academic Performance - Andres, Kayvett Azryll; Babaran, Nilda (International Journal of Arts, Sciences and Education, 2024)
This study employed a cross-sectional non-experimental and correlational design to gather and analyze the data connected to learners’ attitudes in Social Science and their academic performance during the first semester of School Year 2023-2024. A total of 334 students of Isabela State University-San Mariano and Ilagan Campus were selected us using purposive and voluntary sampling technique for the study. Data were collected using a questionnaire designed to assess students’ attitudes towards their Social Science subject and their corresponding academic performance. The findings revealed that learners have positive attitudes toward their Social Science subject, perceiving it as fun and valuable for everyday life and for broader context. The attitudes presented by the learners show relationship with their academic performance; when students have positive attitudes toward Social Science and grasp their societal importance, they tend to excel academically. The study highlights a strong relationship between positive attitudes and educational outcomes, suggesting that interactive learning activities, real-world applications, and student autonomy can enhance engagement and performance. Educators are recommended to explore ways to consistently involve learners in classroom discussions, activities, and decision-making on engagement levels. Furthermore, learners, they are encouraged to explore subjects from multiple point of views, draw connections between various academic fields, and apply what they have learned to actual situations outside the four corners of the classrooms.